Comparing earnings management and creative accounting. A general review - Diana Bachtijeva; Daiva Tamulevičiené (Zeszyty Teoretyczne Rachunkowości, 2022)
Purpose: The aim of this article is to compare the concepts of earnings management and creative accounting and to determine their similarities and differences. Methodology/approach: In the study, it is assumed that earnings management and creative accounting are two different phenomena. A comparative study is carried out in three stages using theoretical study methods. In the first stage, by applying the genetic and historical approaches, the origin and development of earnings management and creative accounting are compared. The purpose of the comparison is to assess the ori-gins, period, and causes of earnings management and creative accounting, and to de-termine the differences in origin and the points of contact. In the second stage, the def-initions of phenomena are compared using comparative analysis methods. In the third stage, using comparative analysis and analogy methods, earnings management tech-niques and creative accounting methods are compared. Findings: The results of the study show that earnings management and creative ac-counting are two terms that describe the same phenomenon. To avoid confusion and ambiguity of the terminology, it is recommended that the term “earnings management” be used. Practical implications: By abandoning the term “creative accounting” and using only the term “earnings management”, a contradiction between the academic community and practitioners, as well as terminological confusion, would be eliminated. Originality/value: The terms “earnings management” and “creative accounting” are used in both different and similar contexts in the literature, and it is difficult to identify which actions describe earnings management and which ones describe creative account-ing. A comparative study of earnings management and creative accounting assists in solving the terminological problems in the literature.